2016
DOI: 10.1159/000445951
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression and Serum Levels of CD44 as Prognostic Indicators in Patients with Non-Small Cell Lung Cancer

Abstract: Background/Objectives: CD44 is often expressed in various types of tumor cells and involved in a number of biological behaviors of malignancy. The present study focused on the clinical significance of the expression of CD44st and CD44v6 in non-small cell lung cancer (NSCLC). Methods: The cohort consisted of 261 consecutive patients who had undergone complete resection of NSCLC. CD44 expression was evaluated in surgical specimens by immunohistochemical staining. Serum CD44 levels were determined using a sandwic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…High expression of CD44 was also reported to be associated with not only occurrence and migration ( 15 ) but also metastasis ( 24 ) and drug resistance ( 19 ) of NSCLC. In the present study, an association between a higher CD44-positive expression rate and higher T stage was observed in NSCLC, which was consistent with the report from Shinohara et al ( 14 ) where significant associations were observed between CD44 expression and clinicopathological factors including T stage, N stage, pathological stage and histological type following immunohistochemical analysis of a cohort consisting of 261 consecutive patients ( 12 ), but the present study failed to identify a significant association between CD44 expression and occurrence or metastasis. This may be due to the small cohort in the present study, so a future study with a large cohort is still required to confirm the association between CD44 expression and other clinicopathological prognosis factors.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…High expression of CD44 was also reported to be associated with not only occurrence and migration ( 15 ) but also metastasis ( 24 ) and drug resistance ( 19 ) of NSCLC. In the present study, an association between a higher CD44-positive expression rate and higher T stage was observed in NSCLC, which was consistent with the report from Shinohara et al ( 14 ) where significant associations were observed between CD44 expression and clinicopathological factors including T stage, N stage, pathological stage and histological type following immunohistochemical analysis of a cohort consisting of 261 consecutive patients ( 12 ), but the present study failed to identify a significant association between CD44 expression and occurrence or metastasis. This may be due to the small cohort in the present study, so a future study with a large cohort is still required to confirm the association between CD44 expression and other clinicopathological prognosis factors.…”
Section: Discussionsupporting
confidence: 94%
“…In previous studies, high expression of CD44 was hypothesized to be associated with poor prognosis in NSCLC ( 14 , 23 ). High expression of CD44 was also reported to be associated with not only occurrence and migration ( 15 ) but also metastasis ( 24 ) and drug resistance ( 19 ) of NSCLC.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The expression of CD44 in metastatic ovarian cancer cells was significantly higher than that in primary ovarian cancer cells [28]. CD44 has been shown to be associated with tumor migration and metastasis in colon cancer and breast cancers,and could be used as a prognostic indicator in lung cancer [29][30][31]. CD44 is the major cellular receptor for HA and in association with HA, CD44 has a certain impact on the activation of cell-survival antiapoptotic proteins, consequently resulting in tumor cell proliferation and tumorigenesis in hepatocellular carcinoma and lung cancers [6,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding of molecular markers of cancer stem cells in NPC can improve the development of clinical strategies, as seen in inhibition of tumor growth by interference with CD44v6 signaling [49] and a specific ALDH1A1 inhibitor for cancer stem cell target therapy [50]. In addition, higher serum CD44v6 levels in lung cancer [51] and joint detection of CD44v6 and CD62P in NPC peripheral blood were found to be significantly unfavorable prognostic factors. Therefore, further studies are needed to apply cancer stem cell markers for therapeutic targets and biomarkers in NPC.…”
Section: Discussionmentioning
confidence: 99%